1999
DOI: 10.1103/physrevlett.83.860
|View full text |Cite
|
Sign up to set email alerts
|

Resonant Inelastic X-Ray Scattering from Valence Excitations in Insulating Copper Oxides

Abstract: We report resonant inelastic x-ray measurements of insulating La2CuO4 and Sr2CuO2Cl2 taken with the incident energy tuned near the Cu K absorption edge. We show that the spectra are well described in a shakeup picture in 3rd order perturbation theory which exhibits both incoming and outgoing resonances, and demonstrate how to extract a spectral function from the raw data. We conclude by showing q-dependent measurements of the charge transfer gap.PACS numbers: 78.70. Ck, 74.25.Jb Inelastic x-ray scattering (… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

11
141
1

Year Published

2000
2000
2016
2016

Publication Types

Select...
4
4

Relationship

1
7

Authors

Journals

citations
Cited by 126 publications
(153 citation statements)
references
References 19 publications
11
141
1
Order By: Relevance
“…Note that both excitations have a direct gap, that is, a minimum energy at the zone center. This observation of q-dependent excitations in the 2 ∼ 4 eV range is broadly consistent with the recent RIXS studies of Ca 2 CuO 2 Cl 2 [11] and of Sr 2 CuO 2 Cl 2 [10], although in these experiments, the coarse energy resolution prevented the authors from being able to resolve any double peak features. In addition, the amount of dispersion observed here along the Cu-O bond direction (∼ 1.0 eV) is almost twice that observed for Ca 2 CuO 2 Cl 2 and in fact is close to that observed in the quasi-one-dimensional cuprate Sr 2 CuO 3 [12].…”
supporting
confidence: 76%
See 1 more Smart Citation
“…Note that both excitations have a direct gap, that is, a minimum energy at the zone center. This observation of q-dependent excitations in the 2 ∼ 4 eV range is broadly consistent with the recent RIXS studies of Ca 2 CuO 2 Cl 2 [11] and of Sr 2 CuO 2 Cl 2 [10], although in these experiments, the coarse energy resolution prevented the authors from being able to resolve any double peak features. In addition, the amount of dispersion observed here along the Cu-O bond direction (∼ 1.0 eV) is almost twice that observed for Ca 2 CuO 2 Cl 2 and in fact is close to that observed in the quasi-one-dimensional cuprate Sr 2 CuO 3 [12].…”
supporting
confidence: 76%
“…As first observed in NiO [8], large enhancement of the inelastic x-ray scattering signal is obtained when the incident x-ray energy is tuned near the transition metal K-edge. To date, a number of insulating cuprates have been studied [9,10,11,12]. While these previous studies provided detailed information on the local resonance processes, they provided only qualitative information on the momentum(Q)-dependence of the CT excitations, mainly due to poor signal-to-noise ratio.…”
mentioning
confidence: 99%
“…This technique was initially applied to NiO; 1 in that case a large enhancement of the inelastic signal with incident photon energy was observed near the Ni K edge. More recently this technique has been applied to various cuprates including high-T c materials 2,3,4,5,6,7,8,9,10,11 and other highly-correlated electron systems. 12,13,14 A recent RIXS study near the Cu K edge in undoped La 2 CuO 4 (LCO) has revealed three features in its charge excitation spectrum.…”
Section: Introductionmentioning
confidence: 99%
“…We note that these three resonance energies correspond to the peaks in x-ray absorption spectra near the Cu Kedge [15]. The intensity at 6 eV likely arises from both the Cu Kβ 5 emission and a charge-transfer type excitation commonly found in the RIXS studies of cuprates [11,12]. Detailed studies of the E i -dependence will be reported elsewhere, and here we fix E i = 8982 eV, and focus on the momentum dependence of the 3 eV feature.…”
mentioning
confidence: 99%
“…In addition, this gives an element specificity that is valuable in studying complex materials such as the cuprate compounds [4,11,12,13,14]. The RIXS experiments were carried out at the Advanced Photon Source on the…”
mentioning
confidence: 99%